Potential Ecological Risk of Heavy Metal Distribution in Cemetery Soils - Amuno, S. A. (Water, Air, & Soil Pollution, 2013)
In this paper, preliminary investigation was conducted to evaluate the potential ecological risk of heavy metals contamination in cemetery soils. Necrosol samples were collected from within and around the vicinity of the largest mass grave in Rwanda and analyzed for heavy metal concentrations using total digestion–inductively coupled plasma mass spectrometry and instrumental neutron activation analysis. Based on the concentrations of As, Cu, Cr, Pb, and Zn, the overall contamination degree (Cdeg) and potential ecological risks status (RI) of the necrosols were determined. The preliminary results revealed that the associated cemetery soils are only contaminated to a low degree. On the other hand, assessment of the potential ecological risk index (RI) revealed that cumulative heavy metal content of the soil do not pose any significant ecological risks. These findings, therefore, suggest that, while cemetery soils may be toxic due to the accumulation of certain heavy metals, their overall ecological risks may be minimal and insignificant.
Keywords: Cemetery soils; Environmental management; Heavy metals; Mass graves

Message from general chairs - Berglund, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Etnografia, lugares da memória e o discurso dos poderes na aldeia dos índios potiguara - Simões, José Manuel (e-hum, 2013)
eoi/doi Deposit-Electronic Object Identifierhttp://eoi.citefactor.org/10.11248/ehum.v6i2.1385RESUMO: A aldeia dos índios Potiguara não é somente um aglomerado de casas e pessoas. Trata-se de um espaço social muito mais complexo, somando ao habitat modelos de parentesco, cruzando práticas culturais e economicas, juntando aos humanos bichos e plantas, rotinas de trabalhos e “libertações” de lazeres. A aldeia Potiguara embora se apresente como singular, ela comunicava e continua a comunicar hoje com redes mais amplas de aldeias rurais e indígenas, gerando transformações culturais e sociais profundas. Embora as alterações marquem as mudanças nos habitos da aldeia Potiguara acredita-se que as práticas culturais que se estendem das festas ao turismo das suas aldeias são tão tradicionais como singulares.PALAVRAS-CHAVES: Aldeia indígena – Espaço social – Práticas culturais – TransformaçõesABSTRACT:The village of Potiguara Indians is not only a cluster of houses and people. This is a social space much more complex, adding to habitat kinship models, crossing cultural and economic practices, joining human animals and plants, work routines and "releases" of leisure.The Potiguara village despite presenting as singular, she communicated and continues to communicate today with wider networks of rural and indigenous villages, generating deep cultural and social transformations. Although the changes mark the changes in the habits of the village Potiguara is believed that cultural practices that extend parties to tourism from their villages are so traditional and unique.KEYWORDS: Indian Village - social area - Cultural practices - TransformationsRecebido: 31/08/2014    Aceito: 01/10/2014
Keywords: Aldeia indígena; Espaço social; Práticas culturais; Transformações